(3GdeRgQ aj Ydhe GddZI hCfhGYgG (B/s - (3GdSjhWj, YHO GdQMef Hf CHj HcQ Hf eMeO LdGd GdOjfs 849-911 (3gLQjs; (3GdLdGd GdSjhWj, YHO GdQMef Hf CHj HcQ Hf eMeO,s 849-911 (3gLQj(B.s; (3TQjOI, GdTQHjfjs ((3GdbGgQI (B:s (3OGQ GdMOjK WHY, fTQ, JhRjY,s, 2010)
(3jYO cJGH (B"(3GdeRgQ aj Ydhe GddZI hCfhGYgG(B" (3ddEeGe LdGd GdOjf GdSjhWj ehShYI TGedI aj Ydhe GddZI GdYQHjI, jYJHQ gPG GdcJGH ef CHQR eDdaGJ GdSjhWj, hbO MXj HGgJeGe cHjQ ef bHd GdHGMKjf hGdOGQSjf ddZI GdYQHjI Ydi eQ GdYUhQ, jZWj GdcJGH fWGbG hGSYG ef Ydhe GddZI, HOAG ef GdbhGYO GdfMhjI hGdUQajI hUhdG Edi GdeYGLe hGdHdGZI, JfXje GdeGOI, jJejR GdcJGH HefgLjI ObjbI aj YQV GdeGOI GdYdejI, hJbSjegG Edi CHhGH haUhd eJSdSdI, LeY GdBQGA, jLeY GdSjhWj aj cJGHg BQGA GddZhjjf hGdfMhjjf GdSGHbjf, hjbGQf HjfgG hjMdd fbGW GdGNJdGa hGdGJaGb, CeKdI JhVjMjI, jSJTgO GdSjhWj HCeKdI cKjQI ef GdbQBf GdcQje hGdMOjK GdTQja hGdTYQ GdYQHj, eeG jSgd age GdfbGW GddZhjI GdeYbOI(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GddZI GdYQHjIs